Ankle Reconstruction in Fibular Hemimelia: New Approach - Hefny, Hany (HSS J, 2016)
BACKGROUND: Fibular hemimelia is a congenital disorder that is characterized by the absence of the fibula that could be either partial or complete. Successful management aims to restore normal weight bearing and normal limb length. The introduction of the Ilizarov method of limb lengthening has provided an attractive alternative to amputation. During lengthening, the tight posterolateral soft-tissue structures, the thick fibrous fibular band, and the shortened Achilles tendon become tighter and transfer a valgus force to the talus and calcaneus, further aggravating the deformity. QUESTIONS/PURPOSES: We have developed a strategy to address this in patients with Paley type III fibular hemimelia via ankle reconstruction that provides posterolateral stability and buttressing of the ankle and hind foot by reconstructing the lateral buttress. This is achieved through excision of the fibrous fibular anlage, centralization of the ankle, restoring talocalcaneal coronal alignment, and reconstruction of the lateral malleolus by transplanting the cartilaginous remnant of the lateral malleolus or by crafting a bone block autograft taken from the iliac crest or tibia. METHODS: A prospective non-randomized clinical trial included ten ankles in eight patients with fibular hemimelia Paley type III (two patients had bilateral deformity). The patients’ ages ranged from 7 to 36 months. RESULTS: After a follow-up ranging from 48 to 96 months, a stable plantigrade foot was achieved in nine ankles; one ankle had residual equinus, five ankles had residual valgus heel, and eight ankles had complete range of motion of the ankle, whereas one patient lost 5° of dorsiflexion. One ankle had equinus deformity. CONCLUSIONS: To achieve satisfactory results, a stable plantigrade foot and ankle is necessary in patients with fibular hemimelia before attempting to equalize limb length discrepancy. It is important to reconstruct the ankle through an extra-articular soft tissue release, anlage resection, osteotomies, and restoring the abnormal talocalcaneal relationship before any attempt to equalize LLD. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11420-016-9524-6) contains supplementary material, which is available to authorized users.